Haematological, Liver Function Parameters and Heavy Metal Assessment of KWMC Workers at Roadside and Mixed Waste Dumpsites in Kwara State, Nigeria - D.T. Ogundele; V.T. Olayemi; F.M. Folaranmi; O.E. Oludele; A.A. Oladejo (Journal of Applied Sciences and Environmental Management)
Allergic and health implications associated with gardening and waste-scavenging necessitated this study. Blood samples of 27 waste-workers and 16 non-waste workers (control) were digested and analysed for Lead, Cadmium, Nickel and Chromium. Samples were analysed for haematological parameters White Blood Cell (WBC), neutrophils, lymphocytes, Liver function parameters aspartate amino transferase (AST), alanine amino transferase (ALT), and alkaline phosphatase (ALP). Mixed solid waste samples from dumpsites and road soils were analysed by Atomic Absorption Spectroscopy. Pb concentrations between 16.0 – 29.5 mg/Kg were found in road soils and least Cd contamination between 0.5 – 2.0 mg/Kg were recorded. Insignificant difference in metals deposit in road soils and mixed solid wastes, except for Pb and Cd were observed. Least deposited metals (Cd, Cr and Ni) had approximately same deposit level and the highest metal deposit was Pb. Zero difference existed between Cr concentrations in blood samples of both groups. However, results showed true difference between baseline Pb and Cd concentrations of the groups. Haematological parameters and liver function values showed insignificant difference in the groups. Lead was the highest heavy metal found in road soil, solid-waste worker’s blood.